Kink Formation Process in Long-Period Stacking Ordered Mg-Zn-Y Alloy. (15th August 2020) - Yamasaki, Shigeto; Tokuzumi, Tsubasa; Li, Wansong; Mitsuhara, Masatoshi; Hagihara, Koji; Fujii, Toshiyuki; Nakashima, Hideharu
Abstract: The formation process of the kink bands in a directionally solidified, polycrystalline, long-period stacking ordered (LPSO) Mg85 Zn6 Y9 phase during compression deformation was investigated. In-situ compression observations by scanning electron microscopy and electron backscattered diffraction analysis revealed that regions with localized crystal orientation rotation appeared before ridge kinks formed as surface relief. In this paper, it is called as pre-kink The observed pre-kinks were composed of two separate regions rotated in opposite directions to each other and distinguished from one another by the three boundaries. A transmission electron microscopy observation revealed that the boundaries of the pre-kink are sub-boundaries consisting of edge dislocation array, and both its ends are terminated within the matrix. These characteristics match the reported that of regular ridge kink boundaries. In addition, while pre-kinks do not possess the ability of complete reversibility, its boundaries are capable of moving elastically. Graphical abstract: Image, graphical abstract